P1115Cardiac SABR for ventricular tachycardia - initial UK experience. (18th June 2020) - Lee, J; Bates, M; Shepherd, E; Thornley, A; Kelland, N; Greenhalgh, D; Atherton, P; Peedell, C; Hatton, M
Abstract: OnBehalf: United Kingdom Cardiac SABR consortium Background: Stereotactic Ablative Body Radiotherapy (SABR) is a novel non-invasive treatment for Ventricular Tachycardia (VT) refractory to standard catheter ablation. 3 UK hospitals have started compassionate use cardiac SABR programmes, and are working in close collaboration. Purpose: To report initial UK experience for treatment of refractory VT with cardiac SABR. Methods: All patients had undergone prior unsuccessful invasive ablation with VT recurrence despite anti-arrhythmic drug (AAD) use. High-resolution CT imaging with 3D reconstruction was combined with 12 lead ECGs of VT and prior invasive +/- non-invasive electrophysiology mapping data to define a cardiac target. Treatment margins were modified to account for cardiac/respiratory motion and to minimise off target treatment to other organs as per clinical SABR practice. Single fraction high dose treatment (20-25 Gy) was delivered by CT guided Linear Accelerator. Patients were assessed regularly with clinical review and remote device monitoring. Results: 3 patients have been treated so far with aetiologies of prior myocarditis, non-ischaemic dilated cardiomyopathy and ischaemic cardiomyopathy. All patients successfully received planned SABR treatment in <1 hour with no peri-procedural complications. Current follow up is to 4 months. Clinical course was variable – patient 1 had a flare of VT post-SABR requiring temporary escalation of AADs before VT was suppressed, patient 2 had initial suppression of VT but died from decompensated heart failure with further VT after 4 weeks, patient 3 had further VT with a different exit site and underwent repeat invasive ablation and escalated AAD use to achieve VT suppression. Conclusions: Cardiac SABR shows promise for VT control, but further experience and trials are needed. Integration of imaging and electrophysiology data to generate accurate targets appears critical. The effect of SABR seems to develop over several weeks after therapy. Patient selection and timing of SABR delivery is important with acknowledgement that competing causes of death exist in patients with refractory VT entering a compassionate use program.